THE EFFECT OF PLEASE STRATEGY AND WRITING INTEREST TOWARD STUDENTS' WRITING SKILL - Dewi - Sartika (English Education Study Program Faculty of Teacher Training and Education, 2018)
The aims of this study are to find out whether there was a significant difference in writing achievement between the students who were taught by using PLEASE strategy and that of those who were not, to find out whether there was an effect of writing interest on the students writing skill to write descriptive text or not, and to find out whether there was an effect of writing interest on the students writing skill who were taught by using PLEASE strategy or not. The samples involved in this study were the seventh-grade students of SMP Negeri 2 Kayuagung, South Sumatera which were divided into two groups; experimental and control groups. The data were gathered by using written test and questionnaire and then were analyzed by using t-test and simple linear regression. The results showed that t-obtained (2.57) > t-table (2.0017) with the degree of freedom 54 (df = 56). It could be concluded that there was a significant difference between the students who were taught by using PLEASE strategy and that of those who were not. The next result showed that there was no effect of writing interest on the students' writing skill (the score t-obtained of the writing variable was 1.14 at a significant of 0.26). After the treatment, the score of the writing variable was 3.34 at a significant level of 0.003. It indicated that there was an effect of writing interest on students’ writing skills who were taught using PLEASE strategy. In conclusion, the students who were taught by using PLEASE strategy could be encouraged to have writing interest so that they could write a descriptive text based on the generic structure given.